High strength steel unlipped channel sections subjected to ETF loading: laboratory testing, numerical simulations and web crippling design - Lan, Xiaoyi (2024)
This paper presents web crippling and structural design of high strength steel unlipped channel sections under end-two-flange (ETF) loading based on experimental and finite element investigations. The experimental programme was composed of six grade S690 and four grade S960 test specimens, and the corresponding test set-up, procedures and results were reported in detail. The web crippling test results were used in the numerical modelling programme to validate the developed FE models, which were then adopted to perform parametric studies to enlarge parameter ranges of the bearing length, web slenderness and inside bend radius. Given that codified design rules for S690 and S960 high strength steel unlipped channel sections undergoing web crippling are absent, the corresponding normal strength steel design provisions, as stipulated in the European code EN 1993-1-3 and American specification AISI S100, were evaluated for their suitability to high strength steel unlipped channel sections. It is shown that the ultimate strength of high strength steel unlipped channel sections nonlinearly increases with increasing bearing length but with decreasing web slenderness and inside bend radius. The design methods of current EN 1993-1-3 and AISI S100 provide inaccurate and scattered resistance predictions for high strength steel unlipped channel sections. Finally, a modified AISI S100 design method and a slenderness-based design method were proposed, which can outperform the codified design methods.